2019
DOI: 10.2147/cia.s186500
|View full text |Cite
|
Sign up to set email alerts
|

<p>Specific higher levels of serum uric acid might have a protective effect on bone mineral density within a Chinese population over 60 years old: a cross-sectional study from northeast China</p>

Abstract: Background and objective: Oxidative stress has been demonstrated to be a mechanism that leads to bone mass reduction, and according to many studies, serum uric acid (UA) is a strong endogenous antioxidant that can protect bone mineral density (BMD). To date, there have been no large-scale, cross-sectional studies based on the population in northeast China to assess the relationship between serum UA and BMD. Therefore, we examined the association between serum UA and BMD among a Chinese population ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 39 publications
4
23
0
Order By: Relevance
“…However, observational data on the relationship of SUA with lumbar spine BMD have been mixed. Four Chinese cross-sectional studies that included postmenopausal women and older adults revealed a positive association of a higher SUA with greater BMD 19 , 33 – 35 , with similar findings among other studies from Asia 13 , 14 , 36 , 37 . In contrast, another Chinese cross-sectional study showed a positive association of SUA with lumbar spine BMD only in postmenopausal women (n = 4256), rather than in men (n = 943) 20 .…”
Section: Discussionsupporting
confidence: 78%
“…However, observational data on the relationship of SUA with lumbar spine BMD have been mixed. Four Chinese cross-sectional studies that included postmenopausal women and older adults revealed a positive association of a higher SUA with greater BMD 19 , 33 – 35 , with similar findings among other studies from Asia 13 , 14 , 36 , 37 . In contrast, another Chinese cross-sectional study showed a positive association of SUA with lumbar spine BMD only in postmenopausal women (n = 4256), rather than in men (n = 943) 20 .…”
Section: Discussionsupporting
confidence: 78%
“…Currently, clinical studies regarding the relationship between sUA and BMD among older adults are limited and controversial. Four cross-sectional studies from China reported a positive correlation between a higher sUA and greater BMD among postmenopausal women and older adults [ 19 – 22 ]. This conclusion was supported by other studies from Asia [ 23 25 ], as well as from the Netherlands and Italy [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies analyzed the association between serum uric acid levels and BMD rather than evaluating the association between hyperuricemia and osteoporosis. In recent studies, the categories of serum uric acid were not described 7 , 26 , 35 , and the authors divided participants according to their median serum uric acid level 11 , tertiles 8 , quantiles 15 , 20 or quintiles 10 . Few studies have included subgroups with serum uric acid levels > 7 mg/dL, indicating hyperuricemia 9 , 10 , but the subgroup was as small as 25/1080 9 and the participants were limited to men aged 40 to 60 years 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies support a protective role for uric acid in bone metabolism disorders, the majority of the studies were conducted in a single institution 10 , 26 , restricted to a single sex 14 , limited to old participants 8 , 9 or the sample sizes were small 7 , 11 . No study stratified the groups by sex and age, and no study performed subgroup analyses according to past medical histories.…”
Section: Introductionmentioning
confidence: 99%